EFEKTIVITAS PELAKSANAAN PERATURAN DAERAH KOTA KUPANG NOMOR 4 TAHUN 2019 TENTANG RENCANAN INDUK KEPARIWISATAAN KOTA TAHUN 2019-2025 DI PANTAI NUNSUI OESAPA DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH KOTA KUPANG - Awa, Paulinus Armando; Yohanes, Saryono; Tupen, Rafael Rape (Petitum Law Journal, 2025)
In Kupang City, the implementation of regional regulations on tourism development on Nunsui Oesapa beach has not been carried out properly. Community empowerment and the development of public infrastructure, public facilities, and tourism facilities have not been carried out optimally in accordance with applicable regulations. In order to optimize income from tourism on Nunsui Oesapa beach, by building adequate public infrastructure, public facilities, and public facilities as well as good community empowerment. The results of this study show that: (1) The effectiveness of Kupang City Regional Regulation Number 4 of 2019 concerning the City Tourism Development Master Plan for 2019-2025 at Nunsui Oesapa Beach in an effort to increase the original income of Kupang City has not been effective, (2) The contribution of income from Nunsui Oesapa beach tourism has not contributed well and (3) Factors that hinder the effectiveness of the implementation of Kupang City Regional Regulation Number 4 of 2019 concerning the City Tourism Development Master Plan for 2019-2025 at Nunsui Oesapa Beach in an effort to increase the original income of the Kupang City area, namely legal implementation factors, facilities and infrastructure factors, land ownership factors, and lack of promotional factors.